Tarbiyah Akhlaq Curriculum For The Elderly (An Analysis Study Of The Book Tanbīh Al-Ghāfilīn Bi Ahādīṡ Sayyidil Anbiyā Wa Almursalīn) - Tsaury, Sufyan; Al Kattani, Abdul Hayyi; Syafri, Ulil Amri (Rayah Al-Islam, 2025)
This study aims to determine the concept of moral education contained in the book tanbihul ghofilin and in the Sukabumi Elderly Social Rehabilitation Service Unit and create a concept of moral education for the elderly. Researchers used descriptive and analytical methods in their research, and to collect data from the field researchers used observation, interviews and document methods. The results showed that the concept of moral education for the elderly aims to instill aqidah Islamiyah which is shohih and free from shirk, to foster the morals of the elderly so that they have good morals, justifying the elderly's worship procedures so that they are in accordance with the guidance of the teachings of the Prophet Muhammad S.A.W. and so that the elderly get husnul khotimah. To achieve this goal, the lessons that will be delivered by murobbi are about Aqidah Islamiyyah, Fiqh Ibadah, Akhlak, and Tajweed or tahsin al-Quran. The methods that can be used for learning are: advice method, story method, parable method, targhib and tarhib method, exemplary method, conversation method, repetition method, habituation method, talqin method and practical method. As for evaluation, namely by means of self-muhasabah, mulahadzoh, mutaba'ah and ishlah.